Factors that lead towards job satisfaction level among employees at Visi Nusajaya Sdn Bhd Petaling Jaya, Selangor / Noraida Mohd Yusof - Mohd Yusof, Noraida (Faculty of Business and Management, 2019)
Job satisfaction is one of the element that every organization should pay more attention in order to make employee stay longer in their job and achieve high satisfaction. A satisfied employee is not just a retained employee but an ambassador for the brand, internally and externally. Job satisfaction is one of the medium that used by employer especially Human Resource Management practices to attract, retain and give motivation toward employees. Thus, in time with increasingly diverse, the ability to navigate and adapt with changes and challenging work are most important components. The purpose of this study was to identify the factor that lead towards job satisfaction level among employees as well as to identify the most influential factor in at factor that lead level towards job satisfaction among employees Visi Nusajaya Sdn Bhd Petaling Jaya, Selangor. This study used convenience sampling technique and online questionnaire as an instrument to collect data. The data from 72% out of 150 employee are collected then evaluated by using Statistical Package for the Social Science (SPSS) Version 22 Software. The result from Multiple Regression analysis indicate that all the elements in this study which is working environment, pay and salary, and promotion have positive significant relationship with job satisfaction. Moreover, Regression Analysis revealed that, pay and salary found to be the most influential variables towards job satisfaction among employees at Visi Nusajaya Sdn Bhd Petaling Jaya, Selangor